Interaction of myo-inositol hexakisphosphate with biogenic and synthetic polyamines. Issue 27 (12th June 2015) - Torres, Julia; Giorgi, Claudia; Veiga, Nicolás; Kremer, Carlos; Bianchi, Antonio
Abstract : myo -Inositol hexakisphosphate (phytate) forms very stable adducts with biogenic and synthetic polyamines in aqueous solution. Abstract : Within all the eukaryotic cells myo -inositol phosphates (Ins P s) are an important group of biomolecules that are potentially related to signaling functions. The most abundant member of this family in nature is Ins P 6 (phytate, L 12− in its fully deprotonated form). The complicated chemical behavior of this molecule demands a great effort to understand its function in the cell medium. In this work we follow our earlier studies on the interaction of Ins P 6 with metal cations by inclusion of polyamines (both biogenic and synthetic) as potential agents to produce stable adducts. The stability constants of Ins P 6 –amine adducts and the relevant thermodynamic parameters Δ G °, Δ H °, and Δ S ° were determined at 37.0 °C and 0.15 M ionic strength by means of potentiometric titrations and isothermal titration calorimetry (ITC). The biogenic amines studied were 1, 4-diaminobutane (putrescine, put), 1, 5-diaminopentane (cadaverine, cad), N -(3-aminopropyl)-1, 4-diaminobutane (spermidine, spd), N, N ′-bis(3-aminopropyl)-1, 4-diaminobutane (spermine, spm), and 1-(4-aminobutyl)guanidine (agmatine, agm), while the synthetic models of longer polyamines were 1, 19-dimethyl-1, 4, 7, 10, 13, 16, 19-heptaazanonadecane (Me2 hexaen), 1, 22-dimethyl-1, 4, 7, 10, 13, 16, 19, 22-octaazadocosane (Me2 heptaen), 1, 25-dimethyl-1, 4, 7, 10, 13, 16, 19, 22, 25-nonaazapentacosane (Me2 octaen) and N, N ′-bis(3-aminopropyl)-1, 3-propanediamine (3, 3, 3-tet). With the aid of molecular modeling, we also studied the structural aspects of molecular recognition in operation. The final result is a balance between many parameters including charge of the species, flexibility of the amines, H-bonds in the adduct, and desolvation processes.